Analisis Ad-Dakhil Bermuatan Israiliyat dalam Tafsir Surah Al-Qalam Ayat 1 - Arbain Arbain (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This study analyzes ad-dakhīl narratives containing isrā’īliyyāt elements in the interpretation of Surah Al-Qalam verse 1, particularly concerning the meaning of the letter “Nun” and the divine oath by the Pen. Employing a library research method with a descriptive-analytical approach, the study identifies several isrā’īliyyāt reports, such as interpretations of “Nun” as a great whale (al-bahamut), ink (dawāt), or as a symbolic letter. Most of these narrations are weak, inconsistent, and fall into the category of ad-dakhīl (extraneous elements) in Qur’anic exegesis. The analysis concludes that the sound interpretation affirms “Nun” as one of the hurūf al-hijā’iyyah (disconnected letters), as maintained by classical scholars. Therefore, the presence of isrā’īliyyāt in the interpretation of Surah Al-Qalam verse 1 should be approached critically to preserve the purity of Islamic creed and the proper understanding of the Qur’an. The study underscores the importance of purifying Qur’anic exegesis from ad-dakhīl elements to maintain doctrinal integrity and scholarly rigor.